Determinants of salespersons tenure in sales career: a study on car sales executives in Malaysia - Zain, Osman M.; Dahari, Zainurin (2011)

(untitled)
Over the last few decades businesses have witness a shift from transaction to a closer relationship management orientation. Marketing scholars have reported a shift of business orientations from products, to sales and finally to marketing. Thus, an extant of literature has reported that marketing orientation was to replace sales orientation. However, the contemporary business orientation indicates the importance of customer-provider relationship that to some extent create loyalty. This phenomenon has help sales orientation from vanishing in business picture, but instead emerges as the largest contributor to most firms’ sales revenues. The core medium that contributes to the success of sales orientation is the salesperson. Thus, this study attempts to assess the degree of determinant factors that are influencing sales career tenure and organisational loyalty. There are few researches that were published regarding factors influencing career tenure in salesmanship in Malaysian perspectives. In order to test for the effects of among others; job satisfaction, organisational commitment, and intrinsic motivation, this study will collect data from 350 samples comprising of automotive sales representatives in the Klang Valley, Malaysia. The findings will open up a new dimension on the possibility of influencing factors that play a significant role in the career tenure and organisational commitment in salesmanship. It is hoped that the findings from this study may assist the companies in taking steps towards retaining their salespersons.